A SWOT Analysis of Integrating Humanities into Medical Sciences Curricula - Najmeh Malekpoor; Farshid Abedi; Morteza Arab-zozani; Khadijeh Farrokhfall (Mashhad University of Medical Sciences, 2024)
Background: Due to the significant developments and unforeseen crises in public health, doctors must be lifelong learners to respond to these challenges. Considering the role of art in medical education, the purpose of this study is to determine the internal (Strengths and Weaknesses) and external (Opportunities and Threats) factors in the integration of medical humanities and arts into medical curricula.Method: This study employed a descriptive-analytical design. The target population was faculty members knowledgeable in arts and medical education. The research instrument was a researcher-made valid questionnaire (α=0.78). SWOT analysis was conducted by matrix. An independent t-test was used to compare the mean scores of the SWOT based on demographic characteristics. The data were analyzed using SPSS version 16.Results: Presence of active faculty members and relevant experts and Proven track record in arts and medical education as special mission were the most effective strengths, while lack of a fixed and forward-looking program was the primary weakness. The presence of the Faculty of Arts at Birjand was the best opportunity, and the instability of managers and some programs in upstream institutions was the biggest threat. The average score of strengths and weaknesses was 2.62 and opportunities and threats were 2.42.Conclusion: The SWOT matrix analysis indicated a strength-opportunity or developmental position. This finding is not influenced by demographic characteristics. In this position, internal strengths outweigh weaknesses, and opportunities exceed external threats. Thus, it is possible to integrate humanities into medical education with strong developmental strategies.